Piranha Pin Fin (PPF) — Advanced flow boiling microstructures with low surface tension dielectric fluids. (November 2015) - Woodcock, Corey; Yu, Xiangfei; Plawsky, Joel; Peles, Yoav
Highlights: Flow boiling of HFE7000 in a new class of structured microchannel, termed 'Piranha Pin Fin' ( PPF ), is studied. Mass fluxes ranging from 1200 to 7000 kg/s/m 2 are used. Heat fluxes up to 700 W/cm 2 are demonstrated. Single and two-phase heat transfer coefficients and Nusselt numbers are presented. Abstract: Flow boiling of HFE7000 in a new class of structured microchannel, termed Piranha Pin Fin ( PPF ), is studied. The novel heat sink consists of an array of 150 micron diameter microstructures entrenched in a 2.4 mm wide silicon channel, with overall device dimensions of 12 by 28 mm. Mass fluxes ranging from 1200 to 7000 kg/s/m 2 are used to dissipate base heat loads up to 700 W/cm 2, provided over a 6 mm 2 heating element located beneath the PPF array. Experimental single phase and flow boiling heat transfer data is presented for two flow configurations within the microdevice — open flow and extraction flow . The effect of system pressure on phase change heat transfer is experimentally examined at operating pressures of 1.4 atm and 2.8 atm. Single and two phase heat transfer coefficients, Nusselt numbers, exit quality, and pressure drop data is presented to develop a comprehensive system-level analysis of the unique heat sink.